A study on aperture admittance of rectangular waveguide terminated in infinite lossy medium of different complex permittivity values - Singh S.; Patre S.R.; Singh S.P. (My University, 2025)
In this paper, variations of aperture admittance of a rectangular waveguide terminated in an infinite lossy medium are studied at 2.45 GHz through simulation using finite element method (FEM) based Ansoft's HFSS software and the simulation results are compared with theoretical results using plane wave spectral technique. The theoretical equation for aperture admittance was solved using MATLAB software. It is found that aperture admittance for this type of termination shows inductive behavior. Also, the simulated variations of aperture admittance with medium complex permittivity are nearly in agreement with the theoretical results. For the analysis and simulation purposes standard rectangular waveguide (WR-340) propagating only TE10 mode is used.